Chronic opioid use is associated with higher antibody response to influenza vaccination in people living with HIV - Dang, Christine M.; Nelson, C. Mindy; Pahwa, Rajendra N.; Tookes, Hansel E.; Feaster, Daniel J.; Singh, Prabhsimran; Rodriguez, Allan E.; Forrest, David W.; Nakamura, Nobuyo; Ghanta, Priya P.; Jayaweera, Dushyantha T.; Iyer, Akshay; et al. (Frontiers in Immunology, 2025)
IntroductionWe previously reported that opioid use disorder (OUD) heightens inflammation in people with HIV (PWH). Underlying inflammation is considered to be detrimental to immune responses to influenza vaccine in PWH. Here, we tested the hypothesis that influenza vaccine responses in PWH with OUD would have a greater compromise than PWH without OUD or in people without HIV (PWoH) with OUD. MethodsWe enrolled 244 participants based on OUD (OP+/-) and HIV status (HIV+/-) into an influenza vaccine study in which we analyzed hemagglutination inhibition (HAI) titer at pre- (T0) and approximately 7 days (T1), 4 weeks (T2), and 6 months (T3) post-vaccination with a seasonal quadrivalent influenza vaccine. The log2 of T2/T0 fold change (FC) for each of the 4 antigens H1N1, H3N2, B1- Victoria, B2-Yamagata and whole vaccine was calculated. Regression modeling was conducted to assess effects of HIV and opioids and other covariates on antibody response. ResultsAll participant groups (39 HIV+OP+, 66 HIV-OP+, 67 HIV+OP- and 71 HIV-OP-) demonstrated increases in HAI titer from T0 to T2 for all 4 antigens and whole vaccine with the HIV+OP- group manifesting the lowest HAI titers. The T2/T0 FC for H3N2, B1, B2, and whole vaccine was greater in both OP+ groups (PWH and PWoH) than in HIV+OP-, and was similar to that in HIV-OP- control group. Significant interactions between HIV+ status and opioid use were observed after controlling for demographics, previous influenza vaccine history, baseline titers, and other substance use.DiscussionInteraction between HIV and opioid use on immune function results in enhanced antibody response to influenza vaccination in PWH.